Advanced numerical strategies for seismic assessment of historical masonry aggregates. (1st June 2020) - Grillanda, Nicola; Valente, Marco; Milani, Gabriele; Chiozzi, Andrea; Tralli, Antonio
Highlights: Comparison among different approaches for the seismic vulnerability of masonry aggregates. Local analyses with a new upper-bound limit analysis based on NURBS and mesh adaptation. Global pushover analyses with the Equivalent Frame Method and 3D FEM with damaging materials. Nonlinear dynamic analyses on detailed 3D FE mesh with CDP model for masonry. All approaches confirm the high vulnerability and provide information on collapse modes. Abstract: Recent seismic events in Italy have emphasized the high vulnerability of masonry buildings in historical centers, which were generally erected in continuity to each other over time, resulting in aggregates of constructions. The study of the seismic behavior of masonry aggregates can turn into a very difficult task, usually because of the difficulties to achieve a complete knowledge of geometrical evolutions, state of the connections between structural units, and interventions carried out in the course of time. A wide number of local collapses has been observed after recent earthquakes in Italy, highlighting that collapse under horizontal loads may take place mainly through failure mechanisms of single portions of the aggregate. According to Italian Code, both global and local analyses can be adopted in the seismic assessment of single structural units. Therefore, the aim of this study is to investigate different approaches for the evaluation of the seismic vulnerability of historical masonry aggregates. A masonry aggregate located in the historical center of Arsita (Central Italy), which was hit by the 2009 L'Aquila earthquake, has been chosen as a representative case study and a wide set of local and global analyses has been carried out. Local analyses have been conducted through a new upper-bound limit analysis based on NURBS and mesh adaptation, and a kinematic limit analysis applied to the most common local mechanisms. Global analyses have been performed through pushover analyses using the Equivalent Frame Method, and pushover and nonlinear dynamic analyses on a detailed FE model with appropriate constitutive laws. Finally, a discussion about the effectiveness of the different analysis approaches is presented with reference to the results obtained in this study.